Sky's bridal train - Hansen, Margo (Mustang, Okla. Tate Publishing & Enterprises, 2011)
Twenty-year-old Sky Hoffman signs a contract to marry a man from the north woords of Minnestoa, whom she's never met.
116137
Keywords: Mail order brides -- Fiction; Frontier and pioneer life -- Minnesota -- Fiction; Minnesota; Romance fiction; Historical fiction; Fiction; Christian fiction